2000
DOI: 10.1037/h0087828
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to community violence and post-traumatic stress symptoms: Mediating factors.

Abstract: Children's perceptions of safety and family conflict were examined as mediators of the relation between exposure to community violence and post-traumatic stress symptoms. Results indicated that exposure to community violence was related to perceptions of decreased neighborhood safety and increased family conflict, and that this, in turn, mediated the impact of violence exposure on children's post-traumatic stress symptoms. Implications for research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 32 publications
10
103
1
Order By: Relevance
“…In this current study, crime-related activities were commonly reported; four of the ten most frequently reported traumatic events were crimerelated. This finding is consistent with research that has reported high incidences of violent crimes in urban, predominantly low-income communities of color [39][40][41]. Moreover, when specific event exposure was examined in this sample of African American women, crimerelated items were significantly associated with various perinatal outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…In this current study, crime-related activities were commonly reported; four of the ten most frequently reported traumatic events were crimerelated. This finding is consistent with research that has reported high incidences of violent crimes in urban, predominantly low-income communities of color [39][40][41]. Moreover, when specific event exposure was examined in this sample of African American women, crimerelated items were significantly associated with various perinatal outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Exposure to community violence is an element of the exosystem that adversely affects family functioning and stress (Overstreet & Braun, 2000), and the experience of community violence has been specifically associated with child maltreatment (Cicchetti & Lynch, 1993;Coulton, Crampton, Irwin, Spilsbury, & Korbin, 2007;Lynch & Cicchetti, 1998;. For example, Lynch and Cicchetti (1998) examined the mutual relationships among community violence, child maltreatment, and children's functioning over a 1-year period.…”
Section: Exposure To Community Violencementioning
confidence: 99%
“…Women victims of violence are at increased risk for depression, post-traumatic stress disorder and suicide attempts (Bassuk, Melick & Browne, 1998;Miller & Finnerty, 1996). Children are affected by witnessing violence in their home or neighborhood environments (Osofsky, 1995;Overstreet & Braun, 2000;Schwab-Stone et al, 1995). Having childhood experiences of trauma or abuse can contribute to women's difficulties in current relationships and parenting (Melnick, 1999;Nicholson, 1998 presentation).…”
Section: Women and Trauma/violencementioning
confidence: 99%